Prevention of mental health problems: rationale for a universal approach. Issue 1 (18th August 2006) - Bayer, J K; Hiscock, H; Morton-Allen, E; Ukoumunne, O C; Wake, M
Abstract : Background and objective: Mental health problems are a public health issue affecting as many as 20% of children in modern communities. Risk factors for externalising and internalising problems can occur in infancy. Infants at high risk live in stressed families with parent mental health problems, substance misuse, relationship conflict, social isolation, financial problems or infant temperamental difficulty. Although current prevention programmes target services to high-risk groups, targeting can stigmatise families and miss many children in need. The addition of universal prevention programmes for all families could address these concerns. This survey assessed the prevalence of infants at risk attending a primary care service as a delivery point for universal prevention. Design: Survey of mothers of 6-month-old infants attending well-child clinics across six government areas of Melbourne, Victoria, Australia, between August and September 2004. A brief survey measured sociodemographic characteristics and the following family risks: maternal depression, anxiety, stress, substance misuse, violence at home, social isolation and infant temperamental difficulty. Results: The survey was completed by 733 mothers, representing 69% of infant births presented to the primary care service. Of these, 39% of infants were classified as at risk for developing mental health problems. The percentage of infants classified as at risk was not markedly dissimilar across socioeconomic levels (low, 42%; middle, 40%; high, 35%). Conclusions: A substantial number of infants attending routine universal primary care are at risk of developing mental health problems. This primary care setting could provide an ideal platform for preventing early externalising and internalising problems via a universally offered, evidence-based parenting programme.